GOVERNANCE, STEWARDSHIP AND SUSTAINABILITY theory, practice and evidence. - Dallas, George S.; Lubrano, Mike ([S.l.] : ROUTLEDGE, 2022)
The first introductory practical guide of its kind, this book brings together principles of corporate governance, investor stewardship and enterprise sustainability in the context of institutional investment. Stewardship codes are developing in diverse markets to provide a framework for responsible institutional investment practices and fiduciary duties for beneficiaries. While codes provide a starting point, the application of stewardship in practical terms can be challenging for many institutional investors. Written by two well-known corporate governance experts, George Dallas and Mike Lubrano,and based on the ICGN training course on stewardship that they developed, this book gives needed clarity, rigor and guidance to practitioners about what we know--and don't know--about stewardship, governance and sustainability. It explores the theoretical foundations of stewardship, linking these to day-to-day decision-making andproviding real-life examples and practical tools to evaluate issues that arise for companies from an environmental, social and governance perspective and generate ideas about how to make investor stewardship a practical reality in similar cases. Investor stewardship and ESG professionals, portfolio managers, senior managers, regulators and finance students will appreciate this unique guide to developing, refining and operationalising investor stewardship capabilities in line with the respected and internationally recognised ICGN policy framework.
Keywords: BUSINESS & ECONOMICS / Finance; Corporate governance; Corporations -- Investor relations; Sustainable development; Institutional investors; Social responsibility of business